(untitled) (Eurasian Research Bulletin, 2022)
Due to the new, promising varieties, peach orchards provide an opportunity to expand their fields, dramatically increase yields, and increase product exports. New peach gardens can be built at the expense of the varieties of the hairless peach with a high internal capacity, “Oqluchchak-3”, “Superlola”, from the feathered “Krasnaya Moskva”, “Vostok”, “Champion”, “Elbert-1”.